PTH-237 Differing risk of small bowel necrosis in patients undergoing oesophagectomy and total gastrfectomy with feeding jejunostomy placement. (22nd June 2015) - Al-Taan, OS; Nyasvajjala, M; Paul, M; Sharpe, D; Ubhi, S; Bowrey, D
Abstract : Introduction: Placement of feeding jejunostomy at the time of oesophagectomy or total gastrectomy has become standard of care at most UK centres. Review of the literature reveals isolated reports of small bowel necrosis, although the frequency of this problem is unclear. Further, it is unclear whether the risk of small bowel problems is similar for patients after gastrectomy as those after oesophagectomy. The aim of this study was to ascertain the frequency of small bowel problems in a cohort of patients undergoing oesophagogastric surgery. Method: Retrospective review of patients undergoing oesophagogastric resection for cancer during the years 2009–2014. Results: The study population comprised 325 patients undergoing oesophagogastric resection with jejunostomy placement (255 oesophagectomy, 70 total gastrectomy). Five patients undergoing total gastrectomy developed small bowel necrosis (5/70, 7%), while this was not observed in any patient undergoing oesophagectomy (0/255, 0%). The table details the time of this complication and the associated factors. All five patients developed small bowel necrosis after initial discharge from intensive care unit to the surgical ward. All patients required laparotomy with small bowel resection with double barrel stoma formation, parenteral nutrition and subsequent reconstruction (6–8 weeks later). Only one patient had a leukocytosis on the day of diagnosis. No laboratory abnormalities were identified in the preceding 24 hr in the other four patients. One patient dies from multi-organ failure, the remaining four were discharged home. Conclusion: Small bowel necrosis and perforation is a serious and life threatening complication of feeding jejunostomy. In our cohort, it was observed exclusively in patients who had undergone total gastrectomy. There were very few antecedent signs of a problem. All patients required laparotomy and small bowel resection. Disclosure of interest: None Declared.